2022
DOI: 10.1101/2022.09.22.22280216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Commercial immunoglobulin products now contain neutralising antibodies against SARS-CoV-2 spike protein which are detectable in patient serum

Abstract: Antibody-deficient patients respond poorly to COVID-19 vaccination and are at risk of severe or prolonged infection. Prophylaxis with anti-SARS-CoV-2 monoclonal antibodies has been considered. We here demonstrate that many immunoglobulin preparations now contain neutralising anti-SARS-CoV-2 antibodies which are transmitted to patients in good concentrations, albeit with significant differences between products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The difficulty in obtaining CCP and the potential for blood‐borne virus transmission make IVIG an attractive alternative. In a study by Upasani et al., 62 it was demonstrated that numerous commercially available IVIG products contain high titers of neutralizing antibodies but with a significant batch‐to‐batch variation. Furthermore, the characterization of recipient‐neutralizing antibody titers before and after transfusion demonstrated a marked increase in neutralization, similar to that in healthy donors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty in obtaining CCP and the potential for blood‐borne virus transmission make IVIG an attractive alternative. In a study by Upasani et al., 62 it was demonstrated that numerous commercially available IVIG products contain high titers of neutralizing antibodies but with a significant batch‐to‐batch variation. Furthermore, the characterization of recipient‐neutralizing antibody titers before and after transfusion demonstrated a marked increase in neutralization, similar to that in healthy donors.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 50% of their cohort did not respond to combination therapy, requiring the addition of a second antiviral for success, which was measured as an increase in the PCR cycle threshold to an undefined level. 59 Also worthy of particular note, Mikulska et al 60 Antiviral therapy in combination with convalescent plasma was described in 11 individuals, five of whom were cohorts of patients with B-cell malignancy treated with r/nirmatrelvir and CCP, as described by Huygens et al, 61 and had a high success rate of 80% (4 of 5 cases). Considering all cases, the success rates for this approach were similar, with 8/11 (73%) patients responding.…”
Section: Multi-modal Therapy With An Antiviral In Combination With Ne...mentioning
confidence: 99%
“…5,19 Collectively, contemporary clinical data provide evidence to support the utility of high-titer convalescent plasma including vax-plasma as antibody replacement therapy in immunocompromised patients. 17,20,21…”
Section: Resultsmentioning
confidence: 99%